Case Report: A patient with metastatic bladder cancer in the stomach - Liu, Shurong; Zhang, Junling; Wang, Xin (Frontiers in Oncology, 2025)
Metastasis of bladder cancer to the stomach was rarely reported before. We reported a case of a 68-year-old woman with metastatic bladder cancer to the stomach. The patient was diagnosed with epithelial cell carcinoma of the bladder and underwent resection of the bladder, the right ureter and right kidney two years ago. One and a half years later, the enhanced CT examination revealed diffuse thickening of the stomach. Gastroscopy showed the gastric mucosa were swollen, congested and stiff. The biopsy of the EUS-FNA (Endoscopic Ultrasound-Guided Fine Needle Aspiration) showed a high likelihood of bladder epithelial tumors. Then the patient underwent a total gastrectomy and immunohistochemistry of the specimen indicated that her tumor tissue was originated from the bladder. We recommend that clinicians remain vigilant for gastric tumors that are metastases from bladder cancer, especially in patients with a previous primary bladder tumor.